2017
DOI: 10.1111/jth.13761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of isolated distal deep vein thrombosis in patients with active cancer: a multicenter cohort study

Abstract: Essentials• Isolated distal deep vein thrombosis (IDDVT) is frequently associated with cancer.• No study has specifically evaluated the long-term clinical course of cancer-associated IDDVT.• Patients with cancer-associated IDDVT are at very high risk of symptomatic recurrence and death.• We observed low rates of major bleeding during anticoagulation.Summary. Background: Although isolated distal deep vein thrombosis (IDDVT) is frequently associated with cancer, no study has specifically evaluated the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
4
28
0
2
Order By: Relevance
“…Second, in our study, we found a 1‐year VTE recurrence at 6% with an overall incidence rate of 6.5 recurrent VTEs per 100 patient‐years in patients with IDDVT and active cancer despite receiving anticoagulant treatment. This was comparable to the findings in two recent studies by Dentali et al and Galanaud et al in which they found a high risk of recurrent VTEs in patients with IDDVT and cancer . These studies together support initial treatment with anticoagulation in this population as the rate of VTE recurrence would presumably be much higher with a serial monitoring approach.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Second, in our study, we found a 1‐year VTE recurrence at 6% with an overall incidence rate of 6.5 recurrent VTEs per 100 patient‐years in patients with IDDVT and active cancer despite receiving anticoagulant treatment. This was comparable to the findings in two recent studies by Dentali et al and Galanaud et al in which they found a high risk of recurrent VTEs in patients with IDDVT and cancer . These studies together support initial treatment with anticoagulation in this population as the rate of VTE recurrence would presumably be much higher with a serial monitoring approach.…”
Section: Discussionsupporting
confidence: 90%
“…Studies to evaluate the long‐term clinical outcomes of IDDVT in cancer patients have been limited. In a recent multicenter retrospective cohort study, Dentali et al described the clinical course of 308 cancer patients diagnosed with an isolated distal DVT . These investigators reported that 99% of their study population received anticoagulation up front (mean treatment duration, 4.2 months) and there were 47 recurrent VTE events during the follow‐up period (incidence rate, 13.2 events per 100 patient‐years).…”
Section: Introductionmentioning
confidence: 99%
“…14 15 Preliminary results from cohort studies suggest that cancer, initial burden of thrombus and degree of thrombus resolution, bilateral presentation, inpatient setting, and patient demographics might explain a significant proportion of the individual risk of recurrence in patients with first acute IDDVT. 8 10 16 17 18 19 The differential role of DVT location may therefore be less relevant in the presence of major risk factors for recurrence, which would then play as the main determinants of patients' prognosis and dictate the duration of anticoagulation; however, this question has not formally been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…While there are various theories on therapeutic intervention in patients with asymptomatic VTE and peripheral DVT, our department is actively working on it. Peripheral DVT patients with cancer have also been shown to have a much poorer prognosis than peripheral DVT patients without cancer (23,24). The revised guidelines of the American College of Chest Physicians (ACCP; 2016) also recommends therapeutic intervention in patients with active cancer and peripheral DVT (25).…”
Section: Box-and-whisker Plot Of D-dimer Analysis Of Vte Patients (A)mentioning
confidence: 99%